2002
DOI: 10.1053/euhj.2001.3116
|View full text |Cite
|
Sign up to set email alerts
|

D-dimer and platelet aggregability are related to thrombotic events in patients with peripheral arterial occlusive disease

Abstract: Elevated level of D-dimer and low platelet aggregation are independent haemostatic predictors of thrombotic events in patients with peripheral arterial occlusive disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
9

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 34 publications
1
27
0
9
Order By: Relevance
“…Higher level of D-dimer has also been found in patients suffering thrombotic reocclusion following femoropopliteal artery angioplasty when compared with patients with maintained patency of the dilatated arterial segment [50]. Additionally, several studies have suggested a positive association between increased D-dimer concentration and future risk of major cardiovascular events, again suggesting the association between hypercoagulability and adverse outcomes in patients with arterial disease [12,51].…”
Section: Activation Markers and Peripheral Arterial Diseasementioning
confidence: 85%
“…Higher level of D-dimer has also been found in patients suffering thrombotic reocclusion following femoropopliteal artery angioplasty when compared with patients with maintained patency of the dilatated arterial segment [50]. Additionally, several studies have suggested a positive association between increased D-dimer concentration and future risk of major cardiovascular events, again suggesting the association between hypercoagulability and adverse outcomes in patients with arterial disease [12,51].…”
Section: Activation Markers and Peripheral Arterial Diseasementioning
confidence: 85%
“…Повышенный уровень D-димера, свидетельствующий об активации ка-скада свертывания крови и отложении фибрина, рассма-тривается многими исследователями в качестве коагуля-ционного предиктора обострений атеротромбоза у раз-личных категорий больных, в первую очередь с вовлечением периферического или нескольких сосуди-стых бассейнов [11][12][13][14]. Потенциальный интерес может представлять определение данного показателя примени-тельно к выполнению плановых процедур ЧКВ, что и бы-ло предпринято в настоящей работе.…”
Section: кардиологический вестник 2 2018unclassified
“…Есть основания полагать, что традиционные шкалы риска мо-гут быть усовершенствованы путем дополнительного уче-та лабораторных маркеров (как это предлагается, напри-мер, для высокочувствительного тропонина и мозгового натрийуретического пептида у больных с фибрилляцией предсердий). Для обсуждаемой в нашей работе категории больных перспективным маркером мог оказаться D-ди-мер, связь которого с обострениями атеротромбоза ранее продемонстрирована во многих проспективных исследо-ваниях и регистрах [11][12][13][14].…”
Section: оригинальные статьиunclassified
See 2 more Smart Citations